Model Loyalitas Pelanggan Klinik Kecantikan - Kamiluddin Kamiluddin (JURNAL ILMIAH MANAJEMEN & BISNIS, 2020)
This study aims to analyze the factors that affect customer loyalty in the city of Palembang. The sample that will be used in this study are customers who regularly visit beauty clinics in Palembang, consisting of men and women from two beauty clinics aged between 15 and 65 years and have been customers for a long time. The sample of respondents consisted of 101 people using a Likert scale questionnaire and analyzed using the SPSS Amos 24 program's Structural Equation Modeling (SEM). The results showed that there was a mediation (intervening) of the satisfaction variable which caused an indirect influence between professional medical professionals and quality. service to customer loyalty has a greater value than direct influence. Service quality has a positive and significant effect on customer satisfaction. This positive influence is significant, so it can be concluded that customer satisfaction has a positive and significant effect on customer loyalty in the Palembang city beauty clinic.